The Relationship Between Family Support and Quality of Life in Breast Cancer Patients Undergoing Chemotherapy at Dr. Adhyatma Regional General Hospital, MPH, Central Java - Laesya Putri Ilmi Afifatul Ulya; Dwi Retnaningsih (International Journal Of Health Science, 2026)
Breast cancer is a disease that occurs when cells in the breast tissue begin to grow and divide uncontrollably, forming lumps or masses. Chemotherapy causes various side effects that reduce the quality of life of patients. Family support plays an important role in improving the quality of life of breast cancer patients. The purpose of this study was to determine the relationship between family support and quality of life in breast cancer patients undergoing chemotherapy at RSUD dr. Adhyatma, MPH Central Java. The type of research used was quantitative non-experimental with a cross-sectional approach. The sample in this study was 38 respondents determined by purposive sampling technique. Data analysis used the Spearman rank test. Most respondents received good family support (57.9%), the quality of life of respondents was quite good (55.3%). There was a significant relationship between family support and quality of life in breast cancer patients undergoing chemotherapy at RSUD dr. Adhyatma, MPH (p-value 0.000) with a correlation coefficient value of 0.569. Families are expected to provide insight into the importance of family support in the quality of life of cancer patients, especially those undergoing chemotherapy.